Real World Experience of Crizotinib in 104 Patients With ALK Rearrangement Non-small-cell Lung Cancer in a Single Chinese Cancer Center - Liu, Chang; Yu, Hui; Long, Qianqian; Chen, Haiquan; Li, Yuan; Zhao, Weixin; Zhao, Kuaile; Zhu, Zhengfei; Sun, Si; Fan, Min; Chang, Jianhua; Wang, Jialei (Frontiers in Oncology, 2019)
Purpose: Our study aimed to provide data on effectiveness, safety of crizotinib treatment, brain metastases, progression patterns, and sequential therapy beyond crizotinib treatment in patients with advanced ALK-positive NSCLC in China. Methods: We reviewed the medical records of crizotinib-treated NSCLC patients with ALK-rearrangement between May 2014 and May 2018 at Fudan University Shanghai Cancer Center. All patients received crizotinib with 250 mg twice daily. Main outcome measures were progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), the second PFS (PFS2), overall survival (OS), and adverse events. Results: One hundred and four patients with ALK-positive NSCLC were included in this retrospective study. ORR and DCR were 82.7 and 98.1%, respectively. The estimated PFS and OS were 13.0 months (95% CI 9.0–17.0 months) and 36.0 months (95% CI 31.0–41.0 months), respectively. Multivariable analysis showed that young age, presence of baseline adrenal gland metastases and non-adenocarcinoma were independent predictive factors for poorer PFS. Presence of baseline adrenal gland metastases, non-adenocarcinoma, intrathoracic progression and shorter crizotinib treatment time were associated with worse OS. Patients without baseline brain metastases (BBM) who were administered with crizotinib as first-line therapy can achieve a significantly longer PFS than those who received crizotinib as second or later line therapy (p = 0.006). For patients with BBM receiving sequential therapy beyond the first disease progression after crizotinib treatment (1st PD), crizotinib beyond progressive disease (CBPD) plus local therapy can lead to a significantly longer PFS2 (67.0 vs. 21.0 weeks; p = 0.046). Additionally, the OS was significantly longer in patients achieving 1st PD who received CBPD plus local therapy than those who did not receive CBPD or local therapy (35.0 vs. 24.0 months, p = 0.041). Presence of brain metastases at any time was in association with worse PFS. No unexpected adverse effects were reported. Conclusions: Crizotinib was effective and well tolerated in Chinese patients with ALK-positive, advanced NSCLC in real-world clinical practice. For patients without BBM, crizotinib as first-line therapy can lead to a longer PFS than second-or later line therapy. CBPD plus local therapy after 1st PD beyond crizotinib is feasible and effective in clinical routine practice.